Narrating Intersectional Perspectives Across Social Scales: Voicing Valerie - Thimm, Viola (Routledge Advances in Feminist Studies and Intersectionality Ser., 2022)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- Acknowledgements -- 1. Setting the Stage and Introducing Key Players -- 2. Voicing Valerie: Narratives By and About Her -- 3. Analyzing Valerie on the Family Scale -- 4. Analyzing Valerie on the Ethno-national Scale -- 5. Analyzing Valerie on the Transnational Scale -- 6. The Road Traveled and Routes to Take -- Index.